Investigation of the effects of culture conditions on cell growth and tetraacetylphytosphingosine production by mutant Wickerhamomyces ciferrii - Eun, Sung Wook; Lee, Pyung Cheon (Process Biochemistry, 2023)
Wickerhamomyces ciferrii is a non-conventional yeast strain characterized by the production of large amounts of tetraacetylphytosphingosine (TAPS). TAPS is an industrially valuable substance that can be converted into bioactive ceramide through deacetylation. TAPS-overproducing W. ciferrii is typically cultured in complex media, but there have been no systematic studies on the development of a defined medium for TAPS production. In this study, the composition of a defined medium for W. ciferrii strain was systematically investigated to increase the TAPS production. Among the defined medium components tested, Zn2+ significantly influenced TAPS production. The modified defined medium devoid of ZnSO4, with 40 g/L glycerol as a carbon source, increased TAPS production by 35% (1.16 ± 0.04 g/L, 0.039 g-TAPS/OD600) compared to the control defined medium (0.8 ± 0.01 g/L, 0.022 g-TAPS/OD600) in flask cultures. In batch bioreactor fermentation using the modified defined medium (40 g/L glycerol), 1.85 ± 0.1 g/L of TAPS (0.046 g-TAPS/g-glycerol, 0.044 g-TAPS/OD600) was achieved, which was 28% higher than 1.45 ± 0.02 g/L of TAPS (0.036 g-TAPS/g-glycerol, 0.027 g-TAPS/OD600) with the complex medium. Therefore, the modified defined medium developed in this study has the potential to serve as a base medium for large- scale TAPS production and for physiological and metabolic engineering studies.
Keywords: Bioactives; Ciferrii; Complex medium; Culture conditions; Deacetylation; Defined mediums; Large amounts; Medium; Tetraacetylphytosphingosine; Yeast strain; Ceramide; Ciferrii; Medium; Tetraacetylphytosphingosine